Evaluation of Quality of Life in Patients with and without Heart Failure in Primary Care - Jorge, Antonio José Lagoeiro (Arq Bras Cardiol, 2017)
BACKGROUND: Heart failure (HF) is a major public health issue with implications on health-related quality of life (HRQL). OBJECTIVE: To compare HRQL, estimated by the Short-Form Health Survey (SF-36), in patients with and without HF in the community. METHODS: Cross-sectional study including 633 consecutive individuals aged 45 years or older, registered in primary care. The subjects were selected from a random sample representative of the population studied. They were divided into two groups: group I, HF patients (n = 59); and group II, patients without HF (n = 574). The HF group was divided into HF with preserved ejection fraction (HFpEF - n = 35) and HF with reduced ejection fraction (HFrEF - n = 24). RESULTS: Patients without HF had a mean SF-36 score significantly greater than those with HF (499.8 ± 139.1 vs 445.4 ± 123.8; p = 0.008). Functional capacity - ability and difficulty to perform common activities of everyday life - was significantly worse (p < 0.0001) in patients with HF independently of sex and age. There was no difference between HFpEF and HFrEF. CONCLUSION: Patients with HF had low quality of life regardless of the syndrome presentation (HFpEF or HFrEF phenotype). Quality of life evaluation in primary care could help identify patients who would benefit from a proactive care program with more emphasis on multidisciplinary and social support.